Temperature effect on expression of recombinant human prethrombin-2 in Escherichia coli BL21(DE3) ArcticExpress - Saronom Silaban; Murniaty Simorangkir; Shabarni Gaffar; Iman Permana Maksum; Toto Subroto (Jurnal Pendidikan Kimia (JPKim), 2019)
Many proteins produced in E. coli accumulate in inclusion bodies. This study aims to detect the role of temperature in reducing the formation of inclusion bodies during recombinant human prethrombin-2expressed in E. coli BL21 (DE3) Arctic Express host. In this study, we created a host growth curve to find out the right time to add an inducer. The inducer used in our experiment was IPTG 0.1 mM. The fermentation process use a temperature of 12°C and 22°C. The results showed that recombinant human prethrombin-2 was successfully expressed as protein soluble using an optimum temperature of 12°C in E. coli BL21 (DE3) Arctic Express. It was indicated from the 63kDa protein band obtained from the soluble fraction on SDS-PAGE. The higher temperature of fermentation increased the amount of protein in the insoluble fraction due. It concluded that the fermentation temperature affect the rate of prethrombin-2 expression.Keywords: E. coli BL21(DE3) ArcticExpress, prethrombin-2, soluble, temperature